A Multicultural Teaching Framework for Physics - Carreon, S. L. M. (Science Diliman: A Journal of Pure and Applied Sciences; Vol 16 No 2 (2004), 2007)
This paper presents a framework for integrating varying cultural elements in the teaching of physics concepts. The framework is based on a study on the effects of a multicultural physics teaching approach on student concept understanding and attitude towards physics.